Analisis Manajemen Perencanaan Kurikulum dalam Menghasilkan Kualifikasi Lulusan Program Studi Pendidikan Bahasa Arab di Indonesia - Hasnil Oktavera; Sutiah; Apri Wardana Ritonga; Ernawati; Bety Dwi Pratiwi (Mantiqu Tayr: Journal of Arabic Language, 2024)
This research aims to analyze the curriculum planning management strategy based on Merdeka Belajar Kampus Merdeka (MBKM) in the Arabic Language Education Study Program in Indonesia in producing graduate qualifications that meet community needs and job demands through online surveys. This research is qualitative in nature by inviting responses from 4 Heads of Study Programs and analyzing curriculum documents for the Arabic Language Education Study Program. The study program criteria are selected to represent State General Universities and State Islamic Religious Universities. The results of the research show that the curriculum planning management strategy carried out in the Arabic Language Education Study Program in Indonesia is: a) Mapping the main and supporting profiles of graduates in accordance with needs and job opportunities, b) Forming a special team to manage the MBKM program, c) Planning a budgeting system funding for the MBKM program with clear regulations, d) Carrying out effective and deep-rooted socialization, e) Increasing lecturer competency, f) Reforming Arabic language learning based on information technology and integrated with multidisciplinary science, and g) Optimizing partnership collaboration with various parties, especially industry. Through this curriculum planning management strategy, 10 profile qualifications for graduates of the Arabic Language Education Study Program suit the needs and demands of the job market. From the results of this research, it is hoped that there will be further mapping of the 10 profile qualifications of graduates of the Arabic Language Education Study Program in Indonesia along with their instruments.